Sex differences in the etiology of disgust sensitivity: A preliminary behavioral genetic analysis. (June 2019) - Olatunji, Bunmi O.; Taylor, Steven; Zald, David
Highlights: For women, each disgust sensitivity (DS) dimension influenced by genetic and environmental factors. 40.1% of the variance in DS in women due to additive genetic factors. Correlations among DS dimensions for women explained by genetic and environmental factors. For men, DS dimensions were influenced by environmental but not genetic factors. Abstract: Evidence suggests that Disgust Sensitivity (DS) is a personality trait that may confer risk for the development of some anxiety-related disorders. To examine the origins of this trait we administered the DS subscale of the Disgust Propensity and Sensitivity Scale-Revised to 90 monozygotic and 90 dizygotic twin pairs, of which 55% were women. The DS subscale consists of two dimensions; Somatic Disgust and Ruminative Disgust. Biometrical modeling techniques were used to estimate heritability of the DS dimensions by sex. For women, each dimension was influenced by a combination of genetic and environmental factors. More specifically, 40.1% of the variance in DS was observed to be due to additive genetic factors and the remaining variance due to non-shared environment. Correlations among DS dimensions for women could be explained by genetic and environmental factors influencing the two dimensions. For men, the two dimensions were influenced by environmental but not genetic factors. These findings suggest that the etiology of DS is complex and arises as a function of dimension-specific and non-specific etiologic factors that vary as a function of sex. The implication of these findings for the sex differences in the etiology of some anxiety-related disorders are discussed.